2013
DOI: 10.7314/apjcp.2013.14.4.2383
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Expression of Recombinant Human Smp30 for Detecting Serum Smp30 Antibody Levels in Hepatocellular Carcinoma Patients

Abstract: Senescence marker protein 30 (SMP30), a hepatocellular carcinoma (HCC) associated antigen, was earlier shown by our research group to be highly expressed in HCC paracancerous tissues, but have low levels in HCC tissues. In order to detect anti-SMP30 antibody in serum of HCC patients, we established pET30a-SMP30 and pColdIII-SMP30 expression systems in Escherichia coli. However, the expression product was mainly in the form of inclusion bodies. In this research, we used several combinations of chaperones, four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…These findings were consistent with the previous reports confirming the positive effects of molecular chaperones on solubility parameter and disaggregation. 21,22,[27][28][29] Among the molecular plasmid chaperones, PG-tf2 exhibited a fairly much more positive effect on solubility of our aggregation-prone hscFv than the other two plasmid chaperones. The efficiency of ptf16 was also higher than that observed for pGro7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with the previous reports confirming the positive effects of molecular chaperones on solubility parameter and disaggregation. 21,22,[27][28][29] Among the molecular plasmid chaperones, PG-tf2 exhibited a fairly much more positive effect on solubility of our aggregation-prone hscFv than the other two plasmid chaperones. The efficiency of ptf16 was also higher than that observed for pGro7.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study has shown that ptf16 promotes the soluble expression of human sequence marker protein 30 (SMP30) more effectively than its counterpart pG-tf2. 28 Watanabe K.I. et.al and colleagues studied the role of different chaperones on soluble expression of human ST6Gal I (hST6Gal I), and showed that chaperon pGro7 is the efficient chaperon of choice for solubility increase of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed with minor modification as previously described (Cen et al, 2012;Zhang et al, 2013). In brief, total protein was extracted from untreated and 5-AZA-CdR-treated glioma cells using a Total Protein Extraction Kit (KeyGen, China) according to the manufacturer's instructions.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Protein extracts from the HCC cell lines and Western blots were performed as described24. Equal amounts of proteins from HCC cell lines were subjected to western blot.…”
Section: Methodsmentioning
confidence: 99%